Analise da soldagem a ponto por resistência elétrica do aço 38MnB5 estampado a quente - Pallu, Lucas Gomes (Universidade Federal de São Carlos, 2021)
With the increasing demand for lighter and safer vehicles one of the solutions is the use of stronger steels that can be formed by hot stamping and with smaller thicknesses, reducing weight and maintaining safety. The 38MnB5 is a steel produced for hot stamping that has the premise of reaching up to 2000 MPa of Tensile Strength depending on the cooling rate applied in the stamping process. Its microstructure after stamping is mostly composed of fine grains of martensite, which enable this high strength. Because it is a recent steel grade in the market, information about welding is still lacking, especially information about resistance spot welding, a process widely used in automotive parts. In this way, a study of resistance spot welding was performed for 38MnB5 steel, the material was characterized to define the mechanical properties initially and after the hot stamping process, where the quenching of the material is carried out. The 38MnB5 grade was hot stamped from an existing production line at Benteler Automotive, to produce the 22MnB5 grade. Because it is a hot process and because the steel used is uncoated, the oxide layer formation takes place as soon as it meets the atmosphere, during the transfer of the plate from the furnace to the stamping tool. Thus, the steel was analyzed for weldability in two different surface conditions: after stamping, containing an oxidized layer; and blasted, where the oxide layer was removed. The 8.8 kA current was the one that presented the best results regarding the size and repeatability of the welded plug. Vickers HV1 microhardness profile was determined on the weld cross section, showing values ranging from 350 to 600 HV. The macrography of the weld cross section together with the microhardness values enable the determination of the base metal, the heat-affected zone, and the fused zone. The microstructure of these weld regions varies between martensite, tempered martensite, and tempered martensite with precipitated ferrite on the pre-austenitic grain boundary. To evaluate the mechanical behavior of the joint, shear testing was performed. The rupture force reached was higher than 13.4 kN for all tested samples, where the samples with oxidation obtained lower repeatability of the results. Both presented a pull-out failure mechanism, which is the preferred mechanism for industrial processes.
Resistance spot welding evaluation of hot formed 38MnB5 steel
Keywords: Conformado quente; Solda resistência; Hot-forming; Resistance spot welding; Press hardenable steels; 38MnB; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO